Screening of Protease Inhibitors with Antibacterial Property from Mangroves of Kerala - Kesav, Sapna; Saidalavi, Basim Karayil; Pannippara, Manzur Ali; Hatha, Ammanamveetil Abdulla Mohamed (Asian Journal of Biological and Life Sciences, 2020)
Plants have long been used as a source of therapeutic agents. They are thought to be important ingredients in many prophylactic medicines. The aim of this study was to screen mangrove plants of Kerala for protease inhibitors (PI) and antibacterial activity. Biological ingredients from the bark and leaves of five different species of mangrove plants collected from Puthuvypin Station of Cochin coast, Kerala were extracted in phosphate buffer and fractionated using ammoniumsulphate. Out of 30 fractions assayed using α-N-benzoyl- DL-arginine-p-nitroanilide (BAPNA), 12 were found to be inhibitory against the protease produced by the bacterium Bacillus sp. MESVP01 isolated from the mangrove rhizosphere sediment. The PI activity was also proved by qualitative caseinolytic plate assay. The mangrove extracts were further analyzed for antibacterial activity against 9 different standard test bacterial cultures. Bark extracts of mangroves; Avicennia officinalis Ao (B), Avicennia marina Am (B), Eexcoecaria agallocha Ea (B) and leaf extract of Sonneratia caseolaris Sc (L) were shown to inhibit the growth of Pseudomonas aerogenosa. The leaf extracts of Rhizophora mucronata Rm (L), Sonneratia caseolaris Sc (L) and Avicennia marina Am (L) inhibited the growth of Staphylococcus aureus. Results indicate that many mangrove species present in Kerala coast are potential source of protease inhibitors and antibacterial agents, which could be turned out in to valuable therapeutic agents.
Keywords: Antibacterial activity; Mangroves; Protease; Protease inhibitor; Therapeutic agents